1. IMPROVE CLINICAL SYMPTOMS OF PATIENTS AFTER HEMORRHOID SURGERY AT VINMEC TIMES CITY HOSPITAL, 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: Describe patient clinical characteristics and effectiveness after hemorrhoid surgery at Vinmec Times City Hospital in 2023. Subject and method: A Cross-sectional descriptive study of 120 patients undergoing hemorrhoid surgery at Vinmec Times City hospital, from March to November 2023. The data collection tool includes 2 parts: Part A collects information on demographics and general characteristics. Part B is a research medical record including content about the patient's clinical characteristics at various times after surgery. Analyze data using SPSS20.0 software, describe percentages and averages. Results: No patient had symptoms of fever, rapid breathing, or rapid pulse. 1.7% of patients had high blood pressure and the rate of low blood pressure was 7-10%. The proportion of patients with postoperative pain gradually decreased from 78.5% at 6 hours after surgery to 25% when discharged from the hospital. There were 02 patients bleeding on the 2nd day after surgery. The proportion of patients with anal discharge decreased from 54.2% at 6 hours after surgery to 30.0% at 48 hours after surgery. The rate of patients with a lot of tenesmus at 6 hours after surgery was 4.2% and no patient had a lot of tenesmus at the time of discharge. Conclusion: Clinical symptoms after surgery in patients with hemorrhoids such as pain, tenesmus, urinary retention, and anal discharge improved over time in the days after surgery. In the future, nurses need to pay attention to the characteristics of this patient's condition when providing care.
Keywords: Hemorrhoid surgery, symptoms after surgery.